2007
DOI: 10.1016/j.biomaterials.2007.04.026
|View full text |Cite
|
Sign up to set email alerts
|

A biomimetic peptide fluorosurfactant polymer for endothelialization of ePTFE with limited platelet adhesion

Abstract: Endothelialization of expanded polytetrafluoroethylene (ePTFE) has the potential to improve longterm patency for small-diameter vascular grafts. Successful endothelialization requires ePTFE surface modification to permit cell attachment to this otherwise non-adhesive substrate. We report here on a peptide fluorosurfactant polymer (FSP) biomimetic construct that promotes endothelial cell (EC)-selective attachment, growth, shear stability, and function on ePTFE. The peptide FSP consists of a flexible poly(vinyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 31 publications
0
76
0
Order By: Relevance
“…Results showed that the peptide bound endothelial cells quantitatively as well as the common RGD motif, but unlike RGD, it did not show any preference for platelet adherence. The positive in vitro results observed by both Marchant 77 and Grinstaff 85 , particularly in regard to endothelial cell over platelet binding, encourage further investigation of these approaches and coating materials.…”
Section: 0 Bioactive Surface Coatingsmentioning
confidence: 95%
See 1 more Smart Citation
“…Results showed that the peptide bound endothelial cells quantitatively as well as the common RGD motif, but unlike RGD, it did not show any preference for platelet adherence. The positive in vitro results observed by both Marchant 77 and Grinstaff 85 , particularly in regard to endothelial cell over platelet binding, encourage further investigation of these approaches and coating materials.…”
Section: 0 Bioactive Surface Coatingsmentioning
confidence: 95%
“…77 This RRETAWA motif has been shown to bind the α 5 β 1 integrin that is present on the surface of endothelial cells but lacking on platelets. Even though the RRETAWA does possess some affinity for the α v β 3 integrin that is present on endothelial cells and platelets, the interaction is significantly weaker than the binding to α 5 β 1 and so platelet adherence will be reduced.…”
Section: 0 Bioactive Surface Coatingsmentioning
confidence: 99%
“…Marchant et al have also investigated the binding of endothelial cells to a CRRETAWAC coating (on PTFE), and they observed normal cell attachment and proliferation over 96 hours without issues. 25 These data suggest that a CRRETAWAC modified surface can support initial attachment and proliferation of HUVEC. The benefit of the non-covalent coating technique of the interfacial peptides can readily be observed in this experiment where a surface such as native polystyrene, which lacks a mechanism for directing biology, was rendered active by incubating with a solution containing the appropriate peptides.…”
Section: Resultsmentioning
confidence: 81%
“…While more than 15 years have passed since its discovery, the sequence has received little applied interest with the notable exception being the work of the Marchant group. 25 As mentioned, the RRETAWA sequence binds α 5 β 1 strongly, and this integrin is predominantly present on endothelial cells (ECs) but not platelets. The motif does possess some affinity for the α v β 3 integrin that is present on both endothelial cells (ECs) and platelets, but this interaction is 5 orders-of-magnitude weaker than the binding to α 5 β 1 and so platelet adherence is tempered overall.…”
Section: Introductionmentioning
confidence: 95%
“…Fibrin has been proposed as a coating: results have been either discouraging (Mooney DJ et al 1996;Kim BS et al 1998;Wake MC et al 1996) or encouraging as regards anti-adhesive action in platelets and perlecan (Mooney DJ et al 1996;Kim BS et al 1998;Wake MC et al 1996); one article reported an elastin-like recombining protein [84,85,88]. Single peptides like RGD, cyclic RGD (Mooney DJ et al 1996;Kim BS et al 1998;Wake MC et al 1996) have also been proposed, but only in vitro studies are available (Walpoth BH et al 2007;Lord MS et al 2009;Jordan SW et al 2007;Tang C et al 2009;Larsen CC et al 2007).…”
Section: Permanent Materialsmentioning
confidence: 99%